Evaluating knowledge resources in R&D organizations in China: An application using Structural Equation Modeling and Analytic Hierarchy Process. (June 2016) - Hu, Yaoguang; Li, Jingwen; Wen, Jingqian; Yan, Yan
This paper aimed to measure the value of knowledge resources and examine the factors influencing separate knowledge resource evaluation in R&D organizations. To accomplish these goals, a knowledge resource evaluation model was developed, using Structural Equation Modeling (SEM) and Analytic Hierarchy Process (AHP) methods, based on the results of 160 respondents from several research institutions in China. A two-stage research framework was also proposed. The analytical results demonstrated that labor value, technology value and utilization value have positive and significant relationships with the value of knowledge resources. The study also measured the weights of the evaluation criteria, sub-criteria, and the score of the value of knowledge resources using the developed model. The findings will facilitate the sharing or transfer of knowledge resources among organizations more effectively and will help knowledge workers mobilize and manage their knowledge resources more effectively in their organizations.